Operational Competence of the Visual Arts Teacher in Art Practice: Interrogating the Underlying Factors - Oriola, Mufutau Oluwakemi; Idowu, Kojusotito Olatunji; Gandonu, Sewanu Peter (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This study is on operational competence of Visual Arts teachers’ art practice, focusing on the factors influencing their competence and its relevance in contemporary contexts of arts education. Drawing upon literature from education, art pedagogy, and teacher training, this study identifies key factors that contribute to the operational competence of Visual Arts practice, including artistic skill, proficiency and reflective practice. Through an analysis of empirical studies and practical insights, the study highlights the visual arts teachers’ own art practice factors. It also underscores the significance of research informed policies and curriculum frameworks that support the holistic development of Visual Arts education and the cultivation of a vibrant artistic community within schools and society at large. It engages qualitative research design. A sample of twelve (12) Visual Arts students and one (1) Visual Arts teacher each from eleven (11) schools within the six Education Districts of Lagos State were purposively selected. Data was obtained using Portfolio Review Rubrics. Thematic Analysis was employed in analysing data gathered. Findings revealed that Visual Arts teachers’ competence in art practice differs in nuances of scope. It also revealed that teachers’ competence in art practice is a determinant of students’ learning outcome in art practice. Based on the findings, recommendations were made that workshops and conferences on art practice and pedagogy be organised for Visual Arts teachers to improve their operational competence in art practice. It further recommended that art teachers’ training curriculum be re-packaged to include more art practice activities than pedagogy so as to adequately build their art practice competence in scope and strength for prospective art teaching career.